DAMPAK PANDEMIC COVID-19 TERHADAP PENDAPATAN DAN KELAYAKAN USAHATANI BAWANG MERAH DI DESA TORONGREJO, KECAMATAN JUNREJO, KOTA BATU - Asnah Asnah; Maria Veronika Soi; Farah Mutiara (Universitas Tribhuwana Tunggadewi, 2022)
Shallots are one of the important strategies for commodities whose price fluctuation is considered as a commodity that can affect inflation. Therefore, shallot farming is important to note. This study aims to analyze the income and feasibility of shallot farming before and during the Covid-19 pandemic. The research location was determined purposively, with a total sample of 45 people selected based on the census method. Methods of data analysis using farming analysis. The results showed that shallot farming in Torongrejo Village, Junrejo District, Batu City before and during the Covid-19 pandemic provided farmers with an average income of IDR 66,424,807.05 per hectare and IDR 152,732,757.00 per hectare. With this income, shallot farming is feasible to develop based on the R/C value of 3,796 before the Covid-19 pandemic and 6,682 during the Covid-19 pandemic. In addition, the price BEP value was IDR 3,906.92 per kg before the Covid-19 pandemic and IDR 3,741.26 per kg during the Covid-19 pandemic. BEP output was 1,559.63 kg per hectare before the Covid-19 pandemic and 1,075.16 kg per hectare during the Covid-19 pandemic. Thus the Covid-19 pandemic does not harm shallot farming at the research location.